Natural History and Incidence of Premature Thelarche in Puerto Rican Girls Aged 6 months to 8 Years Diagnosed Between 1990 and 1995 - Larriuz-Serrano, María Celeste; Pérez-Cardona, Cynthia M.; Ramos-Valencia, Gilberto; Bourdony, Carlos J. (Puerto Rico Health Sciences Journal, 2013)
See manuscript